EFFECT OF GENDER ON FARMERS’ OWNERSHIP, CONTROL AND ACCESSIBILITY TO CLIMATE CHANGE ADAPTATION RESOURCES IN SOUTHWEST NIGERIA - Ogunjinmi, kehinde Oluwaseye; Fakoya, Emmanuel Olugbenga; Banmeke, Tajudeen Oyekunle Amoo; Fapojuwo, Oluwakemi Enitan; Ogunjinmi, Anthony Adenkule (FUDMA JOURNAL OF SCIENCES, 2022)
The ability to access, control and own adaptation resources is a critical factor in determining rural farmersâ€™ adaptive potential and decision-making towards adaptation to climate change. This study investigated the effect of gender on farmersâ€™ accessibility, control and ownership of climate change adaptation resources in Ogun and Ekiti States respectively, Nigeria. Three hundred and fifty eighty men (358) and (222) women farmers were randomly selected through a multi-stage sampling procedure. A pre-tested questionnaire was used to obtain data and analysed with frequency counts, means, percentages, Chi-square. A positive and statistically significant association (P<0.05) existed between the gender of the respondents and their accessibility to adaptation resources, like hoe (Ï‡2= 10.137), wheelbarrow (Ï‡2=5.647), digger (Ï‡2=11.982), sprayers (Ï‡2=11.792), head pan (Ï‡2=9.5599), education (Ï‡2=22.359), grass plant (Ï‡2=9..912), health-care (Ï‡2=13.764), pesticides (Ï‡2=6.391) inorganic fertilizer (Ï‡2=7.876), transportation means (Ï‡2=10.897), average annual income (Ï‡2= 8.026), labour (Ï‡2=12 .557), information (Ï‡2=12.557), and medicinal plants (Ï‡2=11.296). There existed a positive and statistically significant association (P<0.05) between the gender of the farmers and their control of adaptation resources like digger (Ï‡2=14.630), sprayer (Ï‡2=6.631), head pan (Ï‡2=4.811), education (Ï‡2=11.657) transportation (Ï‡2=3.364) and average annual income (Ï‡2=33.013). Also, there existed a positive and significant association (P<0.05) between the gender of the farmers and their ownership of adaptation resources like land (Ï‡2=6.815), water (Ï‡2-4.491), health-care (Ï‡2= 2.088), labour (Ï‡2= 5.992) and sources of information of climate change (Ï‡2=3.595). As a result, gender-responsive intervention is necessary to strengthen men and women farmers’ climate resilience and improve their adaptation capabilities through access to